Pengaruh Penerapan Model Snowball Throwing Terhadap Hasil Belajar Siswa - Maria Ulpa; Sandi Sandi; Emmi Azis (Mathematics Education Study Program, 2025)
This study is an experimental research with a quantitative approach that aims to determine the influence of the application of the Snowball Throwing model on student learning outcomes. The population of this study is grade VIII students of SMP Negeri 2 Ponre with a sample from class VIII A. The data collection method in this study is Test Instruments in the form of pretest and posttest. The data was processed by instrument tests in the form of Question Difficulty Level Test and Discriminating Power Test, and to answer the Research Hypothesis, a Descriptive Statistical Test and an Infernal Statistical Test were carried out using the Normality Test, and the Independent Sample T-test. Based on the results of the research and the data that has been collected, the researcher can conclude that the application of the snowball throwing model has a significant positive effect on the learning outcomes of SMP Negeri 2 Ponre students. his is proven in the paired sample t-Test calculation, the significance value obtained is 0.000, which means this value is more than <0.05. Apart from that, after getting tcount of 15.203 and ttable of 2.05954, it can be concluded that tcount > ttable (15.203 > 2.05954) so that HO is rejected HI is accepted.